Employees’ Use of Sources of Guidance at Work: A Cross-Cultural Comparison Between the United States and Brazil - Athayde, André Luiz Mendes; Torres, Claudio Vaz (Internext, 2022)
Purpose – The objective of this research was to statistically compare employee’s use of sources of guidance (SOGs) at work in the United States and Brazil and discuss results in the light of differences concerning national cultural characteristics. Method – 220 employees from a Brazilian university and 166 employees from an American university filled out a paper-and-pencil questionnaire. Pearson correlation tests (r) and Student t-tests were run to investigate statistically significant differences between the two samples, which were discussed in the light of national cultural characteristics. Main results – Americans presented significantly higher means than Brazilians on Informal Rules and People Outside Organization, and Brazilians presented significantly higher mean than Americans on Formal Rules and Procedures. The discussion showed that some of these differences are compatible with national cultural characteristics. Relevance/Originality – Recognizing the importance and the role of national cultures on individuals’ attitudes and behavior within the organizational environment is fundamental in the search for effective and contextualized management practices. Theoretical/methodological contributions – Up until 2020, only 12 theoretical-empirical studies about SOGs were developed. Hence, the present study theoretically and empirically contributes to knowledge about this very important work-related construct. Social/management contributions – The results suggest to managers, human resource professionals, and psychologists important differences in the attitudes of American and Brazilian employees concerning the use of sources of guidance at work, contributing, for instance, to recruitment and selection processes in multinationals.